An overview on microalgal-bacterial granular consortia for resource recovery and wastewater treatment. (May 2022) - Kant Bhatia, Shashi; Ahuja, Vishal; Chandel, Neha; Mehariya, Sanjeet; Kumar, Pradeep; Vinayak, Vandana; Saratale, Ganesh Dattatraya; Raj, Tirath; Kim, Sang-Hyoun; Yang, Yung-Hun
Graphical abstract: Highlights: Wastewater and its management are a major concern around the globe. Microalgae-bacteria granular consortia are more efficient in wastewater treatment. Interactions among microbes affect consortia structure and function. Granule structure and composition are affected by pH, T, light intensity, etc. Granular consortia are able to remove nutrients, heavy metals, and pollutants. Abstract: Excessive generation of wastewater is a matter of concern around the globe. Wastewater treatment utilizing a microalgae-mediated process is considered an eco-friendly and sustainable method of wastewater treatment. However, low biomass productivity, costly harvesting process, and energy extensive cultivation process are the major bottleneck. The use of the microalgal-bacteria granular consortia (MBGC) process is economic and requires less energy. For efficient utilization of MBGC, knowledge of its structure, composition and interaction are important. Various microscopic, molecular and metabolomics techniques play a significant role in understating consortia structure and interaction between partners. Microalgal-bacteria granular consortia structure is affected by various cultivation parameters like pH, temperature, light intensity, salinity, and the presence of other pollutants in wastewater. In this article, a critical evaluation of recent literature was carried out to develop an understanding related to interaction behavior that can help to engineer consortia having efficient nutrient removal capacity with reduced energy consumption.